(untitled) (Rudarsko-geološko-naftni zbornik, 2022)
Face failure is a typical phenomenon in longwall coal mines that can have a wide range of consequences. Face failure, which includes wall spall and roof collapse occurrences, is a hazardous virus that, if not managed, spreads fast across all stages of coal mining and has the potential to disable the mine. Based on this research, face failure may have a detrimental influence on technical, environmental, community, safety, and economic concerns, and its negative effects will leave an unfavourable legacy for the future. As a result, these impacts can be mitigated by effective management and risk management approaches. The quantitative and qualitative face failure risk model provided in this study has a considerable potential as a suitable tool for decision makers to analyse failure risk. Face failure-related high-risk variables can be discovered using this approach, which also makes comparing various mines easier from a face failure aspect. For validation, the model was evaluated in the Parvadeh, Negin and Pabedana coal mines. The study’s findings revealed that Parvadeh’s face failure risk factor was 5058, indicating a high risk in this mine due to mechanized mining. Furthermore, the scores of the Negin and Pabedana mines were computed as 3019 and 3165, respectively, indicating that they were in the moderate risk category owing to traditional mining.